Pengaruh Perhatian Orang Tua terhadap Kedisiplinan Belajar Matematika - Fauzia Zukli; Haida Fitri; Tasnim Rahmat; M. Imamuddin (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the significant influence of parental attention on the discipline of learning mathematics. The hypothesis in this study is